REGIONAL ORGANIZATIONS OF ASIA, AFRICA, AND NORTH AMERICA IN THE SYSTEM OF CONTEMPORARY INTERNATIONAL RELATIONS - Chystiakova, Iryna; Bilousov, Oleksandr; Kryvdina, Inna (Public Management and Policy, 2025)
The article examines the role of regional organizations in Asia, Africa, North America, and South America within the framework of contemporary international relations. The relevance of the study is explained by the fact that regional institutions are increasingly acting not only as tools of economic integration or political coordination, but also as centers of the emerging multipolar order. The purpose of the research is to identify the specific features of leading regional organizations and to assess their impact on balancing global and national interests. The study employs systematic and comparative analysis, which enables the contrast of different models of regionalism and the definition of their roles in ensuring security, economic development, and political stability. Organizations of the Asia-Pacific region (ASEAN, APEC, SCO) are characterized by multi-level mechanisms of cooperation that combine economic and security dimensions, thereby strengthening the global positions of member states. The African Union, AfCFTA, and ECOWAS demonstrate the continent’s pragmatic course toward creating a common economic market, maintaining political stability, and promoting infrastructural development. In North and Latin America, the OAS, USMCA, and CARICOM play a key role by combining democratic values, trade and economic cooperation, and mechanisms of collective response. The analysis confirms that regardless of the degree of institutionalization, all organizations function as balancing mechanisms between global centers of power and national interests. They emerge as major actors of the 21st century, shaping regional markets, institutions of cooperation, and security tools. Regional organizations significantly enhance political stability, strengthen the competitiveness of their member states, and play a decisive role in shaping the multipolar world order. The practical significance of the research lies in its potential application to inform the formulation of state policy in the field of international relations. The development of Ukraine’s foreign policy strategy and the strengthening of participation in interregional integration processes.